Why Specialized Service Ecosystems Emerge—the Case of Smart Parking in Germany - Sina Zimmermann; Thomas Schulz; Andreas Hein; Alexander Felix Kaus; Heiko Gewald; Helmut Krcmar (Information Systems Frontiers, 2023)
Traffic caused by drivers searching for a free parking space has numerous negative effects, such as increased emissions and noise pollution. Innovative solutions can reduce these negative effects by providing car drivers with better information via a smart parking app. However, smart parking apps currently do not offer overarching solutions which support the entire parking process. Utilizing a service-dominant logic perspective, we examine why such overarching solutions do not emerge, whereas specialized ecosystems flourish. We follow a multiple case study approach and conduct qualitative interviews with three app providers and fourteen associated parking operators in Germany. Our results show how conflicting institutional arrangements at the micro, meso, and macro context levels lead to specialization. Our study deepens the understanding of how conflicting institutional arrangements affect the emergence of service ecosystems, drawing practical recommendations to overcome specialized smart parking apps in favor of overarching solutions.
Keywords: 000; Smart parking; Service-dominant logic; Multiple case study; Institutional arrangements; Service ecosystems